ENHANCING THE COMPETITIVENESS OF ENTERPRISES IN THE FACE OF CONTEMPORARY CHALLENGES AND TRENDS WITH THE USE OF BLOCKCHAIN TECHNOLOGY - Marta Wiśniewska; Jakub Grabowski (Polityki Europejskie, Finanse i Marketing)
The article focuses on blockchain technology as a tool for supporting enterprises’ competitive potential. The subject of the theoretical considerations was the issues related to the competitiveness of enterprises in the face of market changes and contemporary trends, primarily events associated with the outbreak of the COVID-19 pandemic and the war in Ukraine. The main part of the publication was devoted to the determinants of the activity of enterprises on the Polish market concerning the implementation of blockchain technology. The empirical part indicated, among others, the essence and areas of application of blockchain technology in large enterprises and the possibilities of its practical use in the conducted business. The research undertaken aimed to analyse the possibility of treating blockchain technology as a factor in strengthening the competitiveness of enterprises. At the same time, it was found that large enterprises in Poland do not perceive the capabilities of blockchain-based technology, which may result from insufficient knowledge of its operation and functionality. Low awareness of the complexity and versatility of blockchain technology applications in the corporate sector may constitute a barrier to further disseminating this technology.